Experimental Arabic linguistics - Ntelitheos, Dimitrios; Leung, Tommi Tsz-Cheung (Studies in Arabic linguistics ;, 2021)
"This volume is the first systematic attempt to survey current progress in the relatively new field of Experimental Arabic Linguistics. While experimental work on Arabic linguistics has appeared sporadically in several venues in the past, the chapters in this book provide a more coherent picture of the exciting directions which the field is pursuing. They provide insights into the complex nature of the Arabic language and how native speakers process it, using cutting edge experimental methodologies in the fields of phonetics, psycholinguistics, and typical and atypical language development. This volume is of particular interest to scholars, researchers, and students at both the undergraduate and graduate level, in the fields of linguistics and language studies and can be a point of reference for scholars and researchers in the fields of theoretical and experimental Arabic linguistics"--